Transparansi Penyaluran Bantuan Langsung Tunai Dana Desa (BLT-DD) Covid-19 Tahun 2022 (Studi Kasus Di Desa Saibi Samukop Kec. Siberut Tengah Kab. Kepulauan Mentawai) - Baleuma Sakailoat, Georgerius; Suryaningsih; Handrina, Emi (Jurnal Administrasi Publik dan Pemerintahan, 2024)
Transparency is the disclosure of information clearly and easily accessed by the public both internally and externally which aims to build a sense of trust in carrying out government duties. This study aims to find out how transparent the distribution of direct village cash assistance (BLT-DD) covid-19 in 2022 is in the village of saibi samukop,siberut tengah district. The research carried out was qualitative research with data collection methods through observation,interviews,documentation. The object of this research focuses on the saibi samukop village government,sibirut tengah subdistrict,mentawai islands district. The results of this study indicate that the process of willingness and accessibility of transparency documents for the distribution of direct village cash assistance covid-19 in 2022 in saibi samukop village,siberut tengah subdistrict,still lacks information disclosure in distribution in terms of this can be seen from the determination of the names of family cards as recipients which aren't yet on target. Clarity and completeness of information on the distribution of direct village cash assistance covid-19 in 2022 the village government and its stakeholders have not socialized the community regarding the process of receiving BLT-DD. The openness of the process of channeling direct cash village funds information used is in the form of billboards to provide local scale information to the community. Regulations for the distribution of village cash direct assistance haven't been implemented openly based on early research due to maladministration and discriminatory actions against other community groups who are actually entitled to receive such assistance but are not recorded